Cardioprotective Effect of Chloroform Extract of Arcangelisia flava on Doxorubicin-induced Cardiomyopathy - Ramadhan, Andika Dewi; Baroroh, Rizqy Kiromin; Maharany, Dinda; Ulfa, Evi Umayah; Puspitasari, Endah (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2022)
Long-term use of doxorubicin as cancer chemotherapeutic agent would cause tissue toxicity, including cardiotoxicity. Arcangelisia flava is suggested to have cardio protective effect. This study aimed to determine the effect of chloroform extract of A. flava leaves on cardio histopathology of doxorubicin-treated Wistar white male rats. Wistar male rats were divided into four groups (1) control group; (2) doxorubicin 7.5 mg/kgBW intraperitoneally twice (day 1 and 6); (3) doxorubicin + chloroform extract of A. flava leaves 250 mg/kgBW/day orally for 11 days; (4) Chloroform extract of A. flava leaves 250 mg/kgBW/day orallly for 11 days. At the 12th day, the rats were sacrificed; the heart organ was taken to make histopathological preparations and analyzed using HE staining. Vacuolization and necrosis are the parameters used in evaluating this effect. The phytochemical screening was also done to determine the compounds in chloroform extract of A. flava leaves. Based on the HE staining, chloroform extract of A. flava leaves decreased the cardiotoxicity caused by doxorubicin. The phytochemical screening showed that chloroform extract of A. flava leaves contains flavonoid, tannin, alkaloid, and triterpenoid. The cardioprotective effect of chloroform extract of A. flava leaves was suggested to be contributed by the flavonoid, tannin, and triterpenoid.